Property premises intruders detection using face recognition method / Joveni Henry - Joveni Henry (2017)
Nowadays, many issues and news reported about property premises intrusion have raise major concern among the property premises owner and occupants to protect their safety. Every property premises owner have already taken some action to protect their property premises and safety by using all kinds of methods. However, the current action and method that are usually implemented by the owner can be easily violated and not effective. The rapid and constant advances of technology create opportunities to improve on the security especially for property premises. One of the technology that is rapidly advancing is face recognition. Therefore, this project emphasize strongly on developing a system that can detect intruders of property premises by using the face recognition method. This project will focus mainly on the Viola-Jones algorithm for face and facial parts detection, facial geometry distance measure for feature extraction and Similarity Measure algorithm using the Euclidian Distance to perform face recognition. The significance of this project is that this project may increase the effectiveness of any existing security system that uses video camera or webcam as surveillance. The project can recognize a face and also detect intruders successfully. More features and testing for a more accurate result can be done in future works.